Feasibility of introducing integrated rice-fish farming in Hambantota District, Sri Lanka - H. K. R. S. Kumara; K. S. S. Atapaththu; S. S. Herath; N. P. Vidanapathirana; R. M. Kapila Tharanga Rathnayaka; M. M. K. I. Marasinghe (Indian Journal of Fisheries, 2025)
This study examined the feasibility of introducing integrated rice fish farming (IRFF) among rice farmers in the Hambantota District, Sri Lanka, by assessing their knowledge, perceptions, misconceptions, constraints and perceived potentials. A cross-sectional study design with a two-stage sampling procedure was employed. Data were collected from 100 randomly selected farmers under major irrigation schemes using structured questionnaires and individual interviews. Statistical analyses included chi-square tests, Pearson correlation and binary logistic regression to identify factors influencing willingness to adopt. Results showed that younger, better-educated and land-owning farmers with smaller landholdings were more willing to adopt IRFF, while older and more experienced farmers were less receptive. Knowledge and perception were positively associated with feasibility to adopt, whereas constraints had a significant negative effect. Logistic regression confirmed knowledge, perception and constraints as the most decisive predictors of adoption feasibility, with higher knowledge and favourable perceptions substantially increasing feasibility and constraints reducing it. Although myths did not directly affect feasibility, they were negatively correlated with knowledge and perceptions, suggesting an indirect influence. The findings suggest that the feasibility of IRFF adoption may be enhanced by improving farmer knowledge and perceptions through targeted extension and demonstration programs, while addressing institutional and resource-related constraints.  Keywords: Feasibility constraints, Farmer knowledge and perception, Integrated Rice-Fish Farming, Sri Lanka, Technology feasibility